I need some help on this.
I have tried a few things now, which don't work. i.e. converting base of a logarithm and then using substitution, completing square and arriving at nowhere.
Here is the system of equations:
xy = 64
(log y to base x) + (log x to base y) = 5/2
I have tried a few things now, which don't work. i.e. converting base of a logarithm and then using substitution, completing square and arriving at nowhere.
Here is the system of equations:
xy = 64
(log y to base x) + (log x to base y) = 5/2